(untitled) (Journal of Computational Mathematics, 2025)
This paper is concerned with the superconvergence error estimates of a classical mixed finite element method for a nonlinear parabolic/elliptic coupled thermistor equations. The method is based on a popular combination of the lowest-order rectangular Raviart-Thomas mixed approximation for the electric potential/field (φ,θ) and the bilinear Lagrange approximation for temperature u. In terms of the special properties of these elements above, the superclose error estimates with order O(h^2) are obtained firstly for all three com ponents in such a strongly coupled system. Subsequently, the global superconvergence error estimates with order O(h^2) are derived through a simple and effective interpolation post-processing technique. As by a product, optimal error estimates are acquired for potential/field and temperature in the order of O(h) and O(h^2), respectively. Finally, some numerical results are provided to confirm the theoretical analysis.